Demand management - Vines, David; Maciejowski, Jan Marian; Meade, J. E. (London ; Boston : Allen & Unwin, 1983)
This is the second of two volumes on the causes and cure of stagflation - that combination of mass unemployment and rapid inflation that is currently afflicting the mixed economies of the industrially developed world.
Stagflation Vol 2
Includes bibliographical references (p. [296]-297) and index.
rua 09/05/2017
Loans
Keywords: Demand (Economic theory); Supply and demand; Economic policy; Keynesian economics; Macroeconomics; Great Britain